The White Stag - Seredy, Kate (New York Puffin Books, 1965)
Retells the legendary story of the huns' and magyars' long migration from asia to europe, where they hope to find a permanent home
American Corner
Winner Of The John Newbery Medal Book
11
Keywords: English Fiction; English Stories